THE EFFECT OF USING CARROT (Daucus carota L.) LEAF FLOUR IN THE RATION ON SLAUGHTER WEIGHT AND ABDOMINAL FAT OF MALE BALI DUCK - I M. P., Sumerta,; Wibawa, A. A. P. P.; Puspani, E. (Jurnal Peternakan Tropika, 2023)
This study aims to determine the effect of using carrot leaf flour ( Daucus carota L.) in the ration on slaughter weight and abdominal fat of male bali ducks. This research was conducted for 42 days at Jalan Tegal Wangi II Gang Kavling No. 9 Sesetan, Denpasar, Bali. The experiment design used was a completely randomized design (CRD) consisting of 4 treatments and 6 replications. Each experimental plot was filled with 3 male bali ducks aged 14 days with homogeneous weight. The four treatments were ducks fed a ration without carrot leaf meal as control (A), ducks fed with 3% carrot leaf meal (B), ducks fed 6% carrot leaf meal (C), and ducks fed ration with 9% carrot leaf meal (D). The variables observed were slaughter weight, pad fat, mesentery fat, and ventriculus fat. The results showed that the use of carrot leaf flour in treatments B, C dan D in the ration significantly (P<0.05) was able to increase the slaughter weight of male bali ducks in treatments B, C, and D by 4.57%, 27.57% and 10.09% respectively compared to the control (A). The percentage of pad fat significantly (P<0.05) in treatment B decreased by 16.87%, treatment C by 21.08% and treatment D by 23.98% compared to the control, while the percentage of mesentery and ventriculus fat did not show a significantly (P>0.05) on each treatments. Based on the results, it can be concluded that the addition of 3-9% carrot leaf flour in the ration can increase the slaughter weight and decrease the abdominal fat of male bali ducks. Keywords : Male Bali Duck, Abdominal Fat, Carrot Leaf Flour